Praksis Filantropi Mewujudkan Eudaimonia (Menelaah Budaya Kumpul Kope Orang Manggarai dalam Terang Filsafat Pengakuan Axel Honneth): Philanthropic Praxis Realizing Eudaimonia (Examining the Kope Gathering Culture of the Manggarai People in the Light of Axel Honneth's Confessional Philosophy) - Agu, Egidius; Pandor, Pius (Jurnal Filsafat Indonesia, 2024)
The focus of this research is to examine the value of kumpul kope praxis as one of the local wisdom of the Manggarai people. The philanthropic praxis of kumpul kope is indicative in realising eudaimonia. In order to find the value and meaning contained in the praxis of kumpul kope, the author uses a qualitative method by referring to literature research, especially Axel Honneth's philosophy of mutual recognition. The dialogue between the praxis of kumpul kope and Axel Honneth's thought brings out values such as brotherhood, kinship, sociality, solidarity and humanity. Firstly, kumpul kope as a philanthropic axis to realise eudaimonia. Second, kope gathering is an outward expression of recognition. Third, kumpul kope expresses human dignity. In addition to meaning, values such as kinship, brotherhood, sociality, solidarity and humanity were also found. Humans express humanity only in the spirit of mutual recognition.